Poder, discurso e mídia: a espetacularização de imagens no acontecimento da política norte-americana. - Santos, Antonio Genário Pinheiro dos (2015)
This thesis aims to investigate the discursive practices regarding to the work of public image production at the scope of irruption of the discursive event and at the building up of the image spectacle. With French Discourse Analysis as theoretical basis, this research turns to the media operation about the sayings, and their effects, at the discursivization of the presidential election event in the United States, in 2008 and 2012. Having a qualitative dimension and based on the Foucaultean arqueogenealogic method, this is an investigation about the regime of truth and the discursive police that makes the president Barack Obama subjective, and assuring him a space of public visibility at the scope of public image spectacle. Proposing to deal with the tense relationship between power and knowledge, this research turns to the Foucault’s studies considering, at work of image production, the empire of an intentioned media that calls the subject to assume discursive positions, affects the everyday life, produces truth and fabricates the history of the present time. With a bibliographic incursion that brings to bear a discussion about discourse, media and politics – according to the studies from, among others, Foucault (2005, 2006, 2007, 2008a), Pêcheux (1997b, 2008, 2009), Courtine (2003, 2009, 2011), Debord (2002), Gomes (2004) and Silverstone (2005) – it comes to the analysis of sayings about Obama – digital articles from The New York Times and Folha de São Paulo and even covers of Brazilian and international magazines – considering the thematic path of the president politic image oscillation at the 2008 and 2012 elections. Then, this thesis proposes that at the discursivization of American presidential election, the media worked in a strategic way establishing knowledge/power relations and requiring subject-position occupation by building up visibility spectacle and virtualization of reality. Through the control illusion of the sayings and its respective meaning effects, the mass media presented Obama to the world according to different regimes of truth, which made him oscillate from a divine messiah to a global martyrdom, from the worldwide expectations to a dream seller.